Strengthening of existing reinforced concrete structures against progressive collapse - de Araújo Vieira, Andre (2020)
Progressive collapse refers to the catastrophic event of structural collapse caused by an initial action of disproportionately smaller scale. Typical examples of progressive collapse involve total or partial collapse initiating from the failure of a single column. Failure events include the 1968 Ronan Point building collapse in London; the 1995 Murrah Federal building collapse in Oklahoma, and the 2001 World Trade Centre collapse in New York. These events dramatically demonstrated the need for appropriate strengthening strategies to increase the structure’s resilience and prevent such failure modes. Textile-Reinforced Mortar (TRM) is a novel structural material proved very effective in strengthening and seismic retrofitting of existing reinforced concrete (RC) structures. TRM comprises a mesh of fibres woven in at least two directions and impregnated with a cement-based mortar. Recently significant research has been conducted towards optimizing the already established Near-Surface-Mounted (NSM) reinforcement strengthening method for the a-seismic retrofitting of Reinforced Concrete (RC) buildings. This technique introduces additional reinforcement in cut grooves opened in the concrete cover and filled with binder material which usually is epoxy resin or cement-based mortar. The hypothesis underpinning this research project is that an appropriate design of TRM and NSM reinforcement can bare significant advantages for strengthening of an existing reinforced concrete structure vis-à-vis progressive collapse. The methodological approach involved an experimental campaign that was suplemented by numerical simulations. In the former, four half-scaled RC frames were tested in the laboratory. The investigated parameters involved the TRM cover length and the type of flexural strengthening employed, i.e., TRM or NSM reinforcement. The results revealed that improved progressive collapse resistance can be achieved with the strengthening techniques adopted, attending to criteria of ductility and energy absorption capacity. Two simulation strategies were adopted, i..e, a micro and a macromodelling simulation procedure. In the former, a detailed 3D finite element commercial software was used, whereas in the latter a component-based model. A parametric study was conducted with the 3D model to investigate the influence of design and numerical factors. The outcome showed that the increased progressive collapse resistance of the frame was maintained on strengthened specimens regardless the parameter assessed. Moreover, the numerical investigations highlighted key indicators of progressive collapse resistance. The component based model was calibrated using the experimental data and the 3D model results and provided a reliable and cost effective simulation procedure. Furthermore, this model presented significative less oscillation when compared to the 3D one.